2013
DOI: 10.7852/ijie.2013.26.2.124
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Cold Temperature for the Artificial Hibernation of Bombus ignitus Queen Bumblebees

Abstract: Bumblebees are widely used to pollinate various greenhouse crops. Among the different bumblebee species, Bombus ignitus is indigenous to Korea, China, Japan and Russia. B. ignitus undergoes one generation per year, and artificial hibernation is essential for year-round rearing of the bumblebee. Keeping the queens under low-temperature conditions for several months is an effective method for terminating their diapause and promoting colony development. In the present study, we investigated how cold temperature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Therefore, the necessary cold period for B. ignitus queens was determined to be at least 2 mo. Yoon et al (2013) reported that a cold period of at least 2 mo applied 12 d after emergence was found to be the most favorable condition for diapause break in B. ignitus queens.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the necessary cold period for B. ignitus queens was determined to be at least 2 mo. Yoon et al (2013) reported that a cold period of at least 2 mo applied 12 d after emergence was found to be the most favorable condition for diapause break in B. ignitus queens.…”
Section: Resultsmentioning
confidence: 99%
“…The bumblebees B. terrestris and B. hypocrita sapporoensis belong to Hymenoptera, family Apidae, Subfamily Apinae, and are adapted as bumblebees for the pollination of natural vegetation and agricultural plants (9) . Recently, B. terrestris workers have been abundant from the summer through the winter season because of mass artificial bumblebee production.…”
Section: Discussionmentioning
confidence: 99%
“…Bumblebees are some of the most important native pollinators of crops in the United States (Kleijn et al 2015 ), and recently there has been great interest in understanding their biology throughout the life cycle (Liczner and Colla 2019 ; Williams et al 2019a ). Multiple studies (> 10) have monitored diapausing bumblebees in the lab, relating survival rates to environmental factors like temperature or relative humidity (Gretenkord and Drescher 1997 ; Yoon et al 2013 ; Lindsay 2020 ) or to intrinsic physiological factors like body mass (Woodard et al 2019 ; Treanore and Amsalem 2020 ). Many of the studies that target this lifecycle stage are focused on improving methods of husbandry or commercial rearing (Gretenkord and Drescher 1997 ; Beekman et al 1998 ; Yoon et al 2013 ; Lindsay 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies (> 10) have monitored diapausing bumblebees in the lab, relating survival rates to environmental factors like temperature or relative humidity (Gretenkord and Drescher 1997 ; Yoon et al 2013 ; Lindsay 2020 ) or to intrinsic physiological factors like body mass (Woodard et al 2019 ; Treanore and Amsalem 2020 ). Many of the studies that target this lifecycle stage are focused on improving methods of husbandry or commercial rearing (Gretenkord and Drescher 1997 ; Beekman et al 1998 ; Yoon et al 2013 ; Lindsay 2020 ). Conditions experienced by queens in the lab are not always ecologically realistic (e.g., Beekman et al 1998 ).…”
Section: Introductionmentioning
confidence: 99%